PENGARUH PERBEDAAN JENIS UMPAN TERHADAP HASIL TANGKAPAN IKAN SIDAT (ANGUILLA spp) DI KABUPATEN LOMBOK TIMUR - admin admin; MOHAMMAD SUBHAN (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2019)
The purpose of this research is to know the effect of different types of bait on eelcatches (Anguilla spp) in East Lombok Regency conducted in Lengkok River Basin(Labuhan Haji) by using three types of bait ie Frog (fejervarya cancrivora), Eel(Monopterus albus), Earthworm (lumbricus rubelus). The method used in thisresearch is experimental method. The results of eel catches (anguilla spp) during thestudy were 32 heads consisting of 2 types, namely the sidat kembang (anguillamarmorata) and the dog's eel (anguilla bicolor). Data analysis with F test shows thatat 1% test level, F value count> F table (10.43> 6.22), it means that difference of baittype influence to catch eel (anguilla spp). The BNT test shows that the Frog Feed(fejervarya cancrivora) is the most effective type of bait used in eel catching (anguillaspp).